Regional variation in earnings and the retention of NHS staff in Agenda for Change bands 1 to 4 - Isabel Stockton; George Stoye (Institute for Fiscal Studies (IFS), 2024)
In this report, we use administrative payroll data from the Electronic Staff Record, combined with local earnings data from the Annual Survey of Hours and Earnings for the period between 2014 and 2019, to examine the correlation between leaving rates for certain NHS staff groups and measures of local pay across different areas of England.
Keywords: 330; Health and social care; Healthcare; NHS; Labour supply and workforce; Public sector